Methionine and Antioxidant Potential - Jie Yin; Tiejun Li; Yulong Yin (Journal of Antioxidant Activity, 2016)
Methionine (Met) is a nutritionally essential amino acid and has been widely demonstrated to improve cellular oxidative balance and mediate oxidative stress. Met targets reactive oxygen species (ROS) directly by being oxidized to Met sulfoxide (MetO) 1. Met can be metabolized to cysteine (Cys) through transsulfuration pathway, which is further metabolized to glutathione (GSH), taurine, and hydrogen sulfide (H2S). All these metabolites exhibit antioxidant functions in various models (reviewed at 2). More recently, Met also has been demonstrated to enhance cellular oxidative tolerance via pentose phosphate pathway (PPP) 3, which contributes to the balance of cellular reducing power and accelerates the reduction reaction of MetO and GSH oxidative product GSSH back to Met and GSH.
Keywords: Methionine